Perbedaan Harga Diri Ditinjau Dari Pola Asuh Orangtua Pada Anak Jalanan - Suci Fadilah Siregar; Khairuddin Khairuddin (Universitas Medan Area, 2022)
This study aims to determine differences in self-esteem in terms of parenting patterns of street children. Self-esteem is an individual's assessment of both positive and negative and shows the degree to which the individual is able to believe that he is important and valuable and is able to give appreciation, evaluation, approval of himself and how far the individual can like himself. This research uses quantitative methods, with a comparative approach. The sampling technique was incidental sampling, a sample of 95 people. Data analysis using one- way variance, data collection using the Likert scale method through the self-esteem scale and parenting style scale. Based on the results of the analysis where F = 5,397 p = 0.00 0.05, hypothetical calculation of 87.5 and empirical self-esteem of 110.04 with different parenting styles such as: democratic parenting with empirical results 106.87; authoritarian parenting with empirical results 115.69; and and permissive parenting with empirical results 107.45. There is a significant difference in self-esteem in terms of parenting patterns of street children. Based on the results of this study, it can be stated that the hypothesis is accepted.